Integrating Life Skills into Volleyball Training for Positive Youth Development (PYD) - Juhrodin; Yudha Munajat Saputra; Amung Mamun; Yunyun Yudiana (UNIB Press, 2023)
This study aims to investigate whether integrating life skills into volleyball training can enhance life skills development. The study utilized a group experimental design with 40 training participants divided into a control group and an experimental group. The control group received only volleyball training, while the experimental group received volleyball training integrated with sub-dimensions of life skills such as teamwork, goal setting, time management, emotional skills, interpersonal communication, social skills, leadership, and problem-solving. The results of the study showed that the experimental group experienced a significant improvement in life skills development compared to the control group. Integrating life skills into volleyball training can provide effective benefits for training participants, especially in terms of important social and emotional skills in daily life and the workforce. Therefore, integrating life skills into sports training and education can be an effective alternative to comprehensively enhance life skills development. The findings imply that sports coaches and educators should consider incorporating life skills into their training curriculums to provide young individuals with the necessary skills to succeed in their personal and professional lives. Additionally, policymakers can utilize the results of this study to develop strategies and policies promoting life skills education in schools and sports programs. Overall, the study emphasizes the importance of holistic approaches to youth development and highlights the potential benefits of integrating life skills into sports training for enhancing life skills development.